Cyclodextrin Complexes: An Approach to Improve the Physicochemical Properties of Drugs and Applications of Cyclodextrin Complexes - Budhwar, Vikas (Asian Journal of Pharmaceutics (AJP), 2018)
Inclusion complexes have various applications in different fields of drug delivery and pharmaceutical industry due to their ability of complexation with guest molecules and enhancement of the physicochemical properties of guest molecules. Cyclodextrins and their derivatives have the ability to encapsulate the bioactive compounds into its cavity and protect these from the environmental conditions, improve the solubility, bioavailability, and other properties also. The aim of this review is to highlight the advantages of cyclodextrins in the enhancement of physicochemical properties of drugs (such as solubility, stability, bioavailability, permeability, and others), different methods for production and various characterization techniques used for evaluation of complexes. Applications of cyclodextrin complexes in pharmaceutical and other fields are also explained here with examples. Thus cyclodextrins, because of their continuing ability to find several novel applications in drug delivery, are expected to solve many problems accompanied with the delivery of different novel drugs through various delivery routes.